Herpes simplex virus encephalitis despite normal cell count in the cerebrospinal fluid* - Jakob, Nurith Juliane; Lenhard, Thorsten; Schnitzler, Paul; Rohde, Stefan; Ringleb, Peter A.; Steiner, Thorsten; Wildemann, Brigitte (Critical care medicine, 2012)
Objectives: To describe herpes simplex virus encephalitis despite normal cell count in the cerebrospinal fluid in patients with malignoma after whole brain irradiation. Interventions: Blood and cerebrospinal fluid analysis and magnetic resonance imaging. Measurements and Main Results: Three male and two female patients with malignoma and a recent history of whole-brain irradiation presented with impaired consciousness with or without epileptic seizure. Although cerebrospinal fluid analysis revealed a normal cell count, herpes simplex virus DNA was detected in all samples by polymerase chain reaction. Conclusions: In patients with impaired consciousness, epileptic seizure, or temporal lobe symptoms of new onset and a recent history of brain irradiation with normal cerebrospinal fluid, an atypical anergic course of herpes simplex virus encephalitis should be considered. Herpes simplex virus polymerase chain reaction should be used as method of choice to detect herpes simplex virus genomes as early as possible rather than relying on routine cerebrospinal fluid parameters. Importantly, antiviral therapy should be started without delay in any case of faint suspicion and should be continued until herpes simplex virus encephalitis is clearly ruled out. (Crit Care Med 2012; 40:-1308)
Originally published: April 1, 2012
Gesehen am 06.07.2018